Perancangan Augmented Reality Media Edukasi Protokol Kesehatan Berbasis Permainan Papan - Didit Prasetyo; Octaviyanti Dwi Wahyurini (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
Palagan is the name of a board game with a type of card game that has been distributed in the East Java region since the end of 2020 where the game is connected in one big narrative regarding the education of Covid-19 prevention behavior protocols equipped with attractive visual illustrations, Palagan is equipped with an Augmented Reality application as a complementary feature where the advantage is that it can arouse the interest of its users to learn and can make its users feel entertained, the contribution of this research is to map augmented reality content with the theme of health protocol education which is specifically intended for elementary school-aged children as an effort to minimize the gap in the level of compliance with the application health protocols in the community in urban areas.